Pembuatan Daging Analog dengan Proporsi Gluten dan Puree Kacang Merah (Phaseolus Vulgarisl) ditinjau dari Sifat Organoleptik - Salsabila Rizka Ayu Sarjono; Lilis Sulandari; Niken Purwidiani; Ita Fatkhur Romadhoni (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to develop an analog meat product made from a combination of gluten and red bean puree (Phaseolus vulgaris L.), while evaluating its organoleptic properties as a plant-based protein consumption alternative. With rising prices of animal-derived meat and increasing awareness of health and environmental sustainability issues, analog meat offers a solution to satisfy nutritional needs without compromising the taste and experience of consuming actual meat. The research process begins with the selection of raw materials and appropriate processing methods; gluten is chosen for its elastic properties that mimic meat texture, while red beans provide a better taste and nutritional value. Evaluation is conducted through sensory tests on panelists for various parameters such as shape, color, aroma, taste, and texture. Additionally, proximate analysis is performed to measure the moisture content, protein, fat, ash, and crude fiber of the produced product. The research findings indicate that a combination ratio of 50% gluten and 50% red bean puree yields protein content comparable to conventional meat and a lower fat content, making it a healthier option. Panelists also provide positive feedback regarding the taste and texture of the product, with no significant differences among treatments. Therefore, the results of this research are anticipated to contribute to the development of more innovative and nutritious plant-based food products, as well as raise public awareness of the importance of diversifying food consumption towards healthier and sustainable choices.